Incidence and Outcomes of COVID-19 Infection in Heart Transplant Recipients: The USC Experience - Miklin, D. (J Heart Lung Transplant, 2021)
PURPOSE: Heart transplant recipients may be at increased risk for infection and adverse outcomes from infection with coronavirus (Covid-19). Management of these patients is complex, with no standard of care. We sought to describe the incidence and outcomes of coronavirus infection in this unique population. METHODS: Retrospective review of 225 heart transplant patients at a large academic medical center identified 8 patients with laboratory confirmed Covid-19 infection. Laboratory and clinical data were collected from our institution as well as other local hospitals patients had been treated at. Outcomes were followed from March 15, 2020 to October 15, 2020. All data was deidentified. RESULTS: In a cohort of 225 heart transplant patients, 8 patients were identified after testing positive for Covid-19 infection. The mean and median age of patients was 49.8 and 42 years respectively. 63% of patients were male, and 37% of patients were female. The median and mean time from transplant to diagnosis was 4.1 and 4.5 years. The rate of infection for recently transplanted patients was 11%. Two patients (25%) had atherosclerosis, three patients (37.5%) had diabetes, and five patients (62.5%) had hypertension. Four of the patients (50%) were asymptomatic, 3 patients (37.5%) had acute hypoxic respiratory failure, and 1 patient (12.5%) had dyspnea not requiring oxygen at time of presentation. Four patients (50%) were admitted for treatment. Two patients were treated with remdesvir, one patient with tocilizumab, and one patient with lenrolimab. Immunosuppressive regimens were altered in five patients with decreased mycophenolate mofetil dosing, two patients with decreased tacrolimus dosing, and one patient with decreased cyclosporine dosing. Two patients (25%) had evidence of graft injury with mean AlloSure (donor derived cell free DNA) of 0.6%, the remainder were within normal limits. Overall our patient experience resulted in zero mortality, and all 4 admitted patients were discharged home safely. CONCLUSION: In a single center case series 8 patients were identified with Covid-19 infection. 25% of the patients demonstrated evidence of graft injury, and nearly every patient had their immunosuppressive regimen decreased with 100% survival to date. Further investigation is needed to determine long term outcomes and ideal therapeutic regimen for Covid-19 in this unique population.